Chrysostom as Exegete : Scholarly Traditions and Rhetorical Aims in the Homilies on Genesis - Pomeroy, Samuel, (Vigiliae Christianae, Supplements ;, 2022)
To what extent and to what purposes did John Chrysostom engage previous models of Biblical exegesis? In this systematic study of his Homilies on Genesis , new light is shed on the precision of his adaption of works by Basil, Origen, Eusebius of Emesa, and Eusebius of Caesarea, findings set against a wider 'web' of parallels with various other exegetes (e.g. Ephrem, Diodore, Didymus). The cumulative picture is a network of shared knowledge across geographical and ecclesial boundaries which served as creative cache for Chrysostom's discourses. With the metaphors of textual obscurity and word-depth, he prioritized name and word interpretations as a means of producing multiple layers of ethical evaluation.